2011
DOI: 10.1016/j.atmosenv.2011.04.046
|View full text |Cite
|
Sign up to set email alerts
|

A review of uncertainties in atmospheric modeling of mercury chemistry I. Uncertainties in existing kinetic parameters – Fundamental limitations and the importance of heterogeneous chemistry

Abstract: Mercury and its related compounds are widely recognized as global pollutants. The accurate atmospheric modeling of its transport and fate has been the subject of much research throughout the last decade. Atmospheric gas, aqueous and heterogeneous chemistry are expected to occur for Hg-containing specie sand accurate implementation of their chemical parameters is essential for realistic modeling of mercury cycling. Although significant progress has been made, the current state of knowledge of mercury chemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
155
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(156 citation statements)
references
References 85 publications
1
155
0
Order By: Relevance
“…The existence of BrO radical has been reported in the upper troposphere [62,63] and over the southeastern US [5,64]. Due to the rapid exchange between Br and BrO radicals [65] and the much slower oxidation rate of Hg 0 by BrO [18] the field observations of BrO seem to support the dominant oxidation of Hg 0 by Br in the atmosphere. Shah et al [5] found that sensitivity simulations using the GEOS-Chem chemical transport model by either increasing Br concentrations, or using a faster rate constant for the oxidation reaction of Hg 0 byBr, resulted in a better agreement between the modeled results and the aircraft observations.…”
Section: Dominant Gaseous Oxidant For Hg 0 : O 3 /Oh Br or Others?mentioning
confidence: 73%
See 4 more Smart Citations
“…The existence of BrO radical has been reported in the upper troposphere [62,63] and over the southeastern US [5,64]. Due to the rapid exchange between Br and BrO radicals [65] and the much slower oxidation rate of Hg 0 by BrO [18] the field observations of BrO seem to support the dominant oxidation of Hg 0 by Br in the atmosphere. Shah et al [5] found that sensitivity simulations using the GEOS-Chem chemical transport model by either increasing Br concentrations, or using a faster rate constant for the oxidation reaction of Hg 0 byBr, resulted in a better agreement between the modeled results and the aircraft observations.…”
Section: Dominant Gaseous Oxidant For Hg 0 : O 3 /Oh Br or Others?mentioning
confidence: 73%
“…Table 1 lists the gas-phase oxidation reactions of Hg 0 and the reported rate coefficients. As shown in Figure 2 in Subiret al [18], large variations exist in the current reported rate constants of gas-phase oxidation reactions of Hg. Here we discuss recent advances in the understanding of the oxidation of Hg 0 by halogen atoms and NO3 radicals, as well as determining the major oxidant(s) in the atmosphere.…”
Section: Chemical Redox Pathways In the Gas Phasementioning
confidence: 99%
See 3 more Smart Citations